Early Response to the Conflict of Houses of Worship Construction through the CGR (Collaboration Governance Regime) Model in Tangerang Regency, Indonesia - Ismail, Ismail; Rabitha, Daniel; Nugroho, Novi Dwi; Haryanto, Joko Tri (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
The construction of houses of worship in some areas of Indonesia often causes social conflict. In some cases, the conflict of houses of worship can be resolved well and some are not resolved. The establishment of houses of worship in Tangerang Regency, Banten Province, namely the construction of HKBP Rogate, GKBJ Sepatan, and GBI Tanjakan churches also triggered the social conflict. This article aims to reveal the chronology of the conflict over the construction of the three churches and the local government's actions in overcoming the conflict issues that arose. These three cases were studied by researchers using a qualitative approach and analyzed using the CGR (Collaborative Governance Regime) model.  This CGR model analysis is part of the early response of the parties related to the conflict and can reveal the weaknesses, and strengths in the conflict resolution of the establishment of houses of worship. The data collection method uses interview techniques and documentation studies. The findings of this research show that in the three cases of conflict, two cases show an escalating conflict (the emergence of mass action), and one case does not escalate. Conflict resolution against the establishment of the three houses of worship by the government and community leaders can prevent conflict escalation in the form of mass mobilization if the parties succeed in identifying problems at the location. Identification of parties who have the authority to determine the final direction of the conflict, especially those who reject the presence or establishment of houses of worship, is important in conflict resolution efforts. The success of conflict resolution efforts depends on the involvement of all parties who are authorized to determine the end of the conflict.